Interactional competence: Genie out of the bottle. (July 2018) - Plough, India; Banerjee, Jayanti; Iwashita, Noriko
The papers in this special issue provide support for continued scrutiny of interactional competence (IC) as an important component of the speaking construct. The contributions underscore the complex nature of IC and remind us of the multiple factors that affect any construct definition. At the same time, each study offers insights into those factors through their explorations of IC. In this final paper, we first briefly review key findings from the papers that confirm what is already known about IC and that provide new information to our understanding of the construct of IC. After summarizing points of convergence and of divergence, we turn to a discussion of areas that require additional targeted attention and offer four generalizations as starting points for research. In the final section, we take a critical look at the challenges associated with including IC in the speaking construct and the implications of the studies in this special issue for the relationship between IC and proficiency.